Primeiro registro do gênero Anadia (Reptilia: Squamata: Gymnophthalmidae) para Guyana baseado em um enigmático exemplar do monte Kopinang, maciço de Wokomung - Kok, Philippe Jacques Robert; Means, Donald Bruce; Rivas, Gilson Antonio (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2013)
We provide the first record of the lizard genus Anadia (Gymnophthalmidae) from Guyana, based on an enigmatic specimen collected in the Pakaraima Mountain Range and provisionally referred to Anadia escalerae, a species described from a single specimen collected in the highlands of the Venezuelan Guayana. The new locality extends the known distribution of the genus Anadia to approximately 300 km to the SE and represents the easternmost known record for an Anadia species. The collected specimen is described in detail, compared to other known Anadia species, and closely compared to the holotype of Anadia escalerae, from which it differs in several characteristics that are discussed.
Keywords: Anadia escalerae; Distribution extension; Pantepui; Guyana; Wokomung Massif; Venezuela